2004
DOI: 10.1541/ieejpes.124.588
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Lightning-Surge Propagating in Distribution System and Customer's Facility-Surge Characteristics of Grounding Electrodes and Concrete Poles, and Lightning-surge in Customer's Facility-

Abstract: For the establishment of a more effective grounding design, it is necessary to clarify a transient behavior of a grounding system. In order to verify the current dependency of the grounding electrodes in a distribution system and the behavior of the lightning surges into customer's premise through the power lines, experiments were conducted using the 3 MV impulse voltage generator on a full-scale distribution system and a power line surge simulation mock-up constructed for this purpose. As a result, the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The critical value, however, varies by several factors, for example, the cause of the damage which is the direct lightning hit or induced lightning, the lightning protection measures in the customer facility, and the grounding system of the customer facility. In order to clarify the effects of these factors quantitatively, several studies have been conducted energetically [14,15]. It has been reported that about 20% of currents of the direct lightning hits to distribution systems flow into a customer facility and the overvoltage generated on 45°F ig.…”
Section: Basic Concept On the Calculation Of Lightning Risk Componentsmentioning
confidence: 99%
See 4 more Smart Citations
“…The critical value, however, varies by several factors, for example, the cause of the damage which is the direct lightning hit or induced lightning, the lightning protection measures in the customer facility, and the grounding system of the customer facility. In order to clarify the effects of these factors quantitatively, several studies have been conducted energetically [14,15]. It has been reported that about 20% of currents of the direct lightning hits to distribution systems flow into a customer facility and the overvoltage generated on 45°F ig.…”
Section: Basic Concept On the Calculation Of Lightning Risk Componentsmentioning
confidence: 99%
“…It has been reported that about 20% of currents of the direct lightning hits to distribution systems flow into a customer facility and the overvoltage generated on 45°F ig. 3 Lightning attractive area by the antenna of a house the equipments in a customer facility is larger with the T-T grounding system than that with the T-N grounding system [15]. With these results, it is possible to estimate the occurrence probability of lightning damage.…”
Section: Basic Concept On the Calculation Of Lightning Risk Componentsmentioning
confidence: 99%
See 3 more Smart Citations